Pemberdayaan Kemampuan Berbicara Siswa Melalui Pelatihan Debat dan Diskusi di SMP Muhammadiyah Terpadu - Jelita Zakaria; Loliek Kania Atmaja; Tri Dina Arianti (Lembaga Pengembangan Kinerja Dosen, 2024)
Speaking ability is one of the important skills in education and daily life, but students often face obstacles such as lack of self-confidence and minimal opportunities to practice. This study aims to improve students' speaking ability through debate and discussion-based training. This activity is designed to provide students with direct experience in constructing logical arguments, conveying opinions effectively, and interacting in formal and informal forums. The methods used include theory training, debate simulations, and group discussions with periodic evaluations through observation and questionnaires. The results showed a significant increase in students' speaking ability, especially in terms of clarity of idea delivery, argument structure, and courage to speak in public. In addition, this training also had a positive impact on students' critical thinking skills, ability to work together, and self-confidence.